Trafficking regulator of GLUT4-1 (TRARG1) is a GSK3 substrate. Issue 11 (17th June 2022) - Duan, Xiaowen; Norris, Dougall M.; Humphrey, Sean J.; Yang, Pengyi; Cooke, Kristen C.; Bultitude, Will P.; Parker, Benjamin L.; Conway, Olivia J.; Burchfield, James G.; Krycer, James R.; Brodsky, Frances M.; James, David E.; et al.
Abstract : Trafficking regulator of GLUT4-1, TRARG1, positively regulates insulin-stimulated GLUT4 trafficking and insulin sensitivity. However, the mechanism(s) by which this occurs remain(s) unclear. Using biochemical and mass spectrometry analyses we found that TRARG1 is dephosphorylated in response to insulin in a PI3K/Akt-dependent manner and is a novel substrate for GSK3. Priming phosphorylation of murine TRARG1 at serine 84 allows for GSK3-directed phosphorylation at serines 72, 76 and 80. A similar pattern of phosphorylation was observed in human TRARG1, suggesting that our findings are translatable to human TRARG1. Pharmacological inhibition of GSK3 increased cell surface GLUT4 in cells stimulated with a submaximal insulin dose, and this was impaired following Trarg1 knockdown, suggesting that TRARG1 acts as a GSK3-mediated regulator in GLUT4 trafficking. These data place TRARG1 within the insulin signaling network and provide insights into how GSK3 regulates GLUT4 trafficking in adipocytes.